PERBEDAAN KEPUASAN PERNIKAHAN PASANGAN SUAMI ISTRI BERETNIS MINANG DI KABUPATEN AGAM - Andria Rosa; Yuninda Tria Ningsih (Edu Sociata : Jurnal Pendidikan Sosiologi, 2023)
The purpose of this study was to look at differences in marital satisfaction among married couples who are ethnic Minang. The method used in this study is a correlational quantitative research method. The population of this study was a married couple of Minang ethnicity in Agam district. The subjects in this study amounted to 160 people consisting of 80 married couples who live in IV Koto District, Ampek Angkek District and Sungai Pua District. Sampling using cluster sampling technique. The results showed that the value of p = 0.313 > 0.05 which can be concluded that there is no difference in marital satisfaction between Minang ethnic husband and wife.